TUNES OF THE TRADITIONAL CHRISTMAS CAROLS IN THE NORTHERN PART OF MEZŐSÉG (CÂMPIA TRANSILVANIEI) - Zoltán GERGELY (Studia Universitatis Babeş-Bolyai. Musica)
The paper hereby briefly presents the most beautiful Christmas carols of the northern part of Mezőség (Câmpia Transilvaniei) and also the most popular ones. Part of the material I have presented in this paper has been collected by myself (tunes of the carols from Magyarborzás and vice), the rest I have taken from folklore literature on the area. Tunes are presented and analyzed in a chronological order, starting with the oldest ones. My motivation to write on this topic was to present the area of Mezőség (Câmpia Transilvaniei) and the invaluable treasures of its folklore to a larger group of people. On the other hand, I think it is our duty to help these valuable pieces of folklore survives.